2006
DOI: 10.1093/ei/cbj031
|View full text |Cite
|
Sign up to set email alerts
|

Why Do Entrepreneurs Enter Politics? Evidence from China

Abstract: This article examines the determinants of the entrepreneur's political participation by employing a unique matched firm‐institution data set from China. We find that the likelihood of an entrepreneur's participation can be explained by the underdevelopment of markets and market‐supporting institutions. According to our estimates, the probability of entering politics decreases by 8–20% from the mean when the institutional indices improve by one standard deviation. Our findings support the view that the institut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
249
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 370 publications
(257 citation statements)
references
References 45 publications
5
249
0
3
Order By: Relevance
“…Research has suggested that a three-to five-year membership in either of the councils does more to signal social prestige than to deliver any immediate business benefit (O'Brien 1990). The influence of these bodies on the operating government is quite low, as the Communist Party and the government still maintain very strong influence and power over the legislature (Li et al 2006). For instance, NPC representatives are welcome to make suggestions to the government but are forbidden to intervene in legislative and judicial activities (O'Brien 1990).…”
Section: Political Dependence and Csr Reportsmentioning
confidence: 99%
See 1 more Smart Citation
“…Research has suggested that a three-to five-year membership in either of the councils does more to signal social prestige than to deliver any immediate business benefit (O'Brien 1990). The influence of these bodies on the operating government is quite low, as the Communist Party and the government still maintain very strong influence and power over the legislature (Li et al 2006). For instance, NPC representatives are welcome to make suggestions to the government but are forbidden to intervene in legislative and judicial activities (O'Brien 1990).…”
Section: Political Dependence and Csr Reportsmentioning
confidence: 99%
“…Results are available from the authors on request. 6 In previous research, the concept of a CEO's political connection was measured by a dummy variable equal to 1 if the CEO was either a member of the NPC or the CPPCC or a government official (Fan et al 2007, Li et al 2006. However, our theoretical approach distinguishes between membership in political congresses and bureaucratic embeddedness.…”
Section: Endnotesmentioning
confidence: 99%
“…Another distinct feature of the Chinese capital market, which differs from other emerging markets, is the continuing rule of the Communist Party and ongoing ideological discrimination against entrepreneurial ownership, despite a substantial reform of the economy (Li et al, 2006;Li et al, 2008). Previous literature suggests that Chinese entrepreneurial firms are discriminated against for accessing bank loans (Cull and Xu, 2003;Li et al, 2009;Firth et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the strictly regulated IPO market in China provides a direct measurement of the value of political capital in the IPO market 9 . Another distinct feature of the Chinese capital market, which differs from other emerging markets, is the continuing rule of the Communist Party and ongoing ideological discrimination against entrepreneurial ownership, despite a substantial reform of the economy (Li et al, 2006;Li et al, 2008). Previous literature suggests that Chinese entrepreneurial firms are discriminated against for accessing bank loans (Cull and Xu, 2003;Li et al, 2009;Firth et al, 2009).…”
Section: Introductionmentioning
confidence: 99%